2009
DOI: 10.1007/s12665-009-0395-8
|View full text |Cite
|
Sign up to set email alerts
|

An evaluation of the use of renewable energy to pump water in Sacala las Lomas, Guatemala

Abstract: An evaluation has been conducted to establish if using renewable energy is technically and economically feasible to pump water in Sacala las Lomas, Guatemala. A deep groundwater well has been proposed and a multistage pump system is being considered to distribute groundwater to users' homes. A weather station was erected in Sacala to collect site-specific data. Wind velocity, wind direction, solar insolation, temperature, precipitation, and barometric pressure data were collected over a 1-year study period. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 9 publications
(11 reference statements)
0
3
0
Order By: Relevance
“…It was concluded that the generated electrical energy was not sufficient for the pumping system. It was also concluded that this system was not economical, but it could be economical when compared with the installation of the grid line in the areas where there was no electrical grid system [18]. By Dursun and his colleagues, the performance analyses of the photovoltaic, wind turbine and fuel cell power generation systems were made for the Aegean region [19].…”
Section: Design Construction and Implementation Of Low Cost Photovolmentioning
confidence: 99%
“…It was concluded that the generated electrical energy was not sufficient for the pumping system. It was also concluded that this system was not economical, but it could be economical when compared with the installation of the grid line in the areas where there was no electrical grid system [18]. By Dursun and his colleagues, the performance analyses of the photovoltaic, wind turbine and fuel cell power generation systems were made for the Aegean region [19].…”
Section: Design Construction and Implementation Of Low Cost Photovolmentioning
confidence: 99%
“…This aspect differentiates the course from traditional engineering service learning courses that are project driven. 4,6,7,8,10,11,14 One of the main goals of the course is to integrate social, engineering, and professional issues. More specifically, the course examines the following issues through field study including:…”
Section: Course Structure and Contentmentioning
confidence: 99%
“…The sponsor, the Redevelopment offices of the San Lucas Mission prefers that the project fully or partially utilize alternative energy sources such as geothermal, solar, or wind. In a feasibility study for a similar project in Guatemala, Granich and Elmore found that for economical and land utilization reasons, alternative energy for pumping water was not practical 14 . Nevertheless, the feasibility portion of project in San Lucas will continue because the circumstances of the land use and the terrain of the region are different.…”
Section: Ongoing and Future Projectmentioning
confidence: 99%